Biofilm formation by Candida auris isolated from colonising sites and candidemia cases. Issue 8 (9th June 2019) - Singh, Rachna; Kaur, Mahaldeep; Chakrabarti, Arunaloke; Shankarnarayan, Shamanth A.; Rudramurthy, Shivaprakash M.
Summary: Background: Candida auris, an emerging nosocomial pathogen, exhibits phenotypic variation. Non‐aggregating C. auris isolates display greater biofilm‐forming capacity and virulence than aggregate‐forming isolates. Most of the studies till date have focused on clinical isolates. The biofilm‐forming capacity of colonising isolates remains uninvestigated. Objectives: The present study aimed to elucidate the biofilm‐forming capacity of the colonising isolates of C. auris, correlate it with their aggregation behaviour and antifungal susceptibility, and compare it with that of the isolates from blood‐stream infection. Methods: Colonising and clinical (candidemia) isolates of C. auris were screened for aggregation behaviour, biofilm‐forming capacity and antifungal susceptibility testing. Aggregation behaviour was assessed microscopically. Biofilm‐forming capacity was determined on 96‐well flat‐bottomed microtitre plates. Antifungal susceptibility testing was performed by broth microdilution assay. Results: Aggregative and non‐aggregative phenotypes were found to be predominantly associated with colonising and clinical isolates, respectively, with the former ones being stronger biofilm producers in the colonising group. Non‐aggregative isolates in the colonising group showed lower susceptibility to amphotericin B and fluconazole than aggregative isolates. In contrast, no association was noted between biofilm formation, aggregation behaviour and antifungal susceptibility amongst the clinical isolates. Conclusion: Biofilm formation is a strain‐dependent trait in C. auris, strongly associated with the type and phenotypic behaviour of the isolates. Colonising isolates of this fungus were found to be predominantly aggregative in nature, with a higher biofilm‐forming capacity than non‐aggregative ones.